Would the width of a metal rib spreader affect postoperative pain in patients who undergo video-assisted mini-thoracotomy (VAMT)? - Wang, Linlin; Ge, Lihui; Fu, Ninghua; Ren, Yi (Frontiers in Oncology, 2022)
Background: Hitherto, no study has evaluated postoperative pain in patients with non-small cell lung cancer (NSCLC) treated with video-assisted mini-thoracotomy (VAMT). In this study, we aimed to assess postoperative pain related to the width of the metal rib spreader in patients who underwent lobectomy using VAMT. Methods: Between March 2019 and May 2022, we retrospectively analyzed the results of 94 consecutive patients with NSCLC at our institution, who underwent lobectomy using VAMT. We divided the patients into groups according to the width ratio of the rib spreader to the width of a single intercostal space. Width ratios that measured ≤ 2.5 times were assigned to group A and those that measured > 2.5 times were assigned to group B. Pre-, intra-, and postoperative data were collected and reviewed. Results: We successfully performed VAMT in 94 patients with NSCLC. Forty-five patients were in group A and 49 patients were in group B. There were no intraoperative mortalities, but one patient, due to respiratory failure, had a 30-day mortality. There were no significant differences between the two groups in terms of blood loss, operative time, drainage time, postoperative complications, length of hospital stay, or number of lymph node stations explored and retrieved. The drainage volume (D1–D3) was higher in group B than in group A (P < 0.05). Postoperative visual analog scale (VAS) pain scores were significantly lower at 12, 24, and 48 h (P < 0.05), and there was no significant difference in VAS scores between the two groups at 72 h and 1 week postoperatively (P > 0.05). Conclusion: The smaller the width of the metal rib spreader used in surgery, the less pain experienced by the patient and the faster the recovery. Multicentre, randomised, controlled trials should be conducted in the future.